Overlapping synthetic peptides as a tool to map protein-protein interactions ̶FSH as a model system of nonadditive interactions - Santa Coloma, Tomás Antonio (2022)
Fil: Santa Coloma, Tomás Antonio. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina